2000
DOI: 10.1097/00000539-200001000-00033
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Residual Pain on Oxygenation and Breathing Pattern During Morphine Analgesia

Abstract: Pain relief with regional analgesia in patients previously treated with opioids increases the incidence of abnormal respiratory events associated with oxygen desaturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Indeed, several studies and case reports indicated an important role of pain in the maintenance of breathing. Combes et al [9] demonstrated in patients treated postoperative pain by i.v. morphine that complete pain resolution by supplemental peripheral nerve block worsened respiratory depression.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, several studies and case reports indicated an important role of pain in the maintenance of breathing. Combes et al [9] demonstrated in patients treated postoperative pain by i.v. morphine that complete pain resolution by supplemental peripheral nerve block worsened respiratory depression.…”
Section: Discussionmentioning
confidence: 98%
“…22 Of 1616 monitoring hours in 103 patients, 342 episodes of desaturation with pulseoximetry monitoring were noted, and 710 notification pages were generated 36% of the time for clinically relevant desaturation. 23 Nursing response time was 52.1 seconds (confidence interval, 46.4-57.7 seconds), which was longer at night (63.8 seconds [confidence interval, 51.2-76.35 seconds]; P = .035). This delay in response to alarms at night was unrelated to unit staffing patterns.…”
Section: Naloxone Usementioning
confidence: 94%
“…Patients who received morphine patient-controlled analgesia (PCA) after knee surgery, and whose pain was then completely abolished by a nerve block, subsequently manifested an increased incidence of oxygen desaturation an d obstructed airwa y events. 16 Borgbjerg et al 17 examined the effects of experimental pain stimulation on the ventilatory response to carbon dioxide-and morphine-induced (0,2 mg/kg IV) respiratory depression in 10 healthy volunteers. Experimental pain stimulated respiration and abolished morphine-induced respiratory depression.…”
Section: Infl Uence Of Painmentioning
confidence: 99%
“…1 The purpose of this paper is to re-examine the known features of morphine-induced respiratory depression and to revise its characteristics in the light of newer pharmacokinetic-pharmacodynamic (PKPD) research. This will be done by means of a case presentation and applied PKPD modelling of a patient who died after a 2010; 16(2) S Afr J Anaesthesiol Analg tonsillectomy, and around whom the discussion will revolve.…”
Section: Introductionmentioning
confidence: 99%